HUTAN DALAM KARYA SENI GRAFIS - SUGIONO HARIYANTO, Yofita Sandra, S.Pd., M.Pd., Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2018)
This final paper aims to visualize the forest in graphic artwork. almost every forest country has always been a hot topic of conversation. Forest destruction is also always a conversation that has never been discussed. Forest is the breath of life of the earth. Forest is the lungs of the earth, if the forest dies then the earth must die including humans who inhabit the earth. The method of creation of this final paper uses five stages: preparation stage, elaboration stage, synthesis stage, and concept realization phase begins sketching, sketching move, tool and material preparation, process of work and finishing. The final stage is the completion to the exhibition art 10.Kata kunci: Hutan,Seni Grafis